1998
DOI: 10.1152/ajpcell.1998.274.3.c724
|View full text |Cite
|
Sign up to set email alerts
|

ATP stimulation of Na+/Ca2+exchange in cardiac sarcolemmal vesicles

Abstract: In cardiac sarcolemmal vesicles, MgATP stimulates Na+/Ca2+exchange with the following characteristics: 1) increases 10-fold the apparent affinity for cytosolic Ca2+; 2) a Michaelis constant for ATP of ∼500 μM; 3) requires micromolar vanadate while millimolar concentrations are inhibitory; 4) not observed in the presence of 20 μM eosin alone but reinstated when vanadate is added; 5) mimicked by adenosine 5′- O-(3-thiotriphosphate), without the need for vanadate, but not by β,γ-methyleneadenosine 5′-triphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
80
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(88 citation statements)
references
References 37 publications
7
80
1
Order By: Relevance
“…Regulation by Phosphorylation-Early experiments suggested that ATP played an important regulatory role in NCX1 function (26,64,65). Possible roles for ATP were "direct" regulation or through phosphorylation of NCX1.…”
Section: Regulators and Ncx1mentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation by Phosphorylation-Early experiments suggested that ATP played an important regulatory role in NCX1 function (26,64,65). Possible roles for ATP were "direct" regulation or through phosphorylation of NCX1.…”
Section: Regulators and Ncx1mentioning
confidence: 99%
“…The intracellular loop also contains a regulatory Ca 2ϩ binding site, Na ϩ association site, sites for H ϩ regulation, and a "XIP" binding site. Although definite view on the spatial organization of the intracellular loop will await a structural investigation of this part of the protein, the preliminary data to date suggest that these regions of association in the intracellular loop interact.Regulation by Phosphorylation-Early experiments suggested that ATP played an important regulatory role in NCX1 function (26,64,65). Possible roles for ATP were "direct" regulation or through phosphorylation of NCX1.…”
mentioning
confidence: 99%
“…The dominant pathway of PIP 2 synthesis, as in other cells, is probably the sequential phosphorylation in the sarcolemma of phosphatidylinositol (PI) at the 4-and then the 5-positions of inositol (66). As in other cells, PIP 2 is hydrolyzed by PLCs to generate IP 3 and DAG, or it can be dephosphorylated to PIP and PI. DAG can be phosphorylated to generate phosphatidic acid (PA) by DAG kinases, which may be regulated by translocation to the surface membrane (32,45), and dephosphorylation of PA can probably be an important source of DAG in heart (for example, see Ref.…”
mentioning
confidence: 99%
“…Third, there are no reliable pharmacological tools to inhibit individual mechanisms involved in PIP 2 metabolism. Fourth, quantitative measurements of PIP 2 are more problematic than measurements of IP 3 . One recent innovation, which overcomes some of these problems, is to monitor the membrane association of green fluorescent proteincoupled PIP 2 -binding domains (57,62).…”
mentioning
confidence: 99%
See 1 more Smart Citation